Critical review on disposition of chlorinated paraffins in animals and humans. (May 2022) - Darnerud, Per Ola; Bergman, Åke
Graphical abstract: Highlights: Based on human and animal data, the review presents ADME data on CPs, and suggests further research needs. Thousands of CP isomers are absorbed and accumulated in humans and wildlife. Numerous CP metabolite reactions are suggested, of which chain shortening (CO2 ) and GSH conjugates are shown in vivo. CPs are of major health concern but properties of CP metabolites, including their toxicity, are still unknown. Future metabolism and toxicity studies of CPs are strongly encouraged. Abstract: Even though the chlorinated paraffins (CPs) have been on the environmental pollution agenda throughout the last 50 years it is a class of chemicals that only now is discussed in terms of an emerging issue with extensive annual publication rates. Major reviews on CPs have been produced, but a deeper understanding of the chemical fate of CPs, including formation of metabolites in animals and humans, is still missing. Thus, the present review aims to critically compile our present knowledge on the disposition, i.e. Adsorption, Disposition, Metabolism, and Excretion (ADME) of CPs in biota and to identify research needs. We conclude that CPs could be effectively absorbed from the gastro-intestinal tract (GI) tract, and probably also from the lungs, and transported to various organs. A biphasic elimination is suggested, with a rapid initial phase followed by a terminal phase, the latter (e.g., fat tissues) covering half-lives of weeks and months. CPs are metabolized in the liver and excreted mainly via the bile and faeces, and the metabolic rate and type of metabolites are dependent on chlorine content and chain length. Results that strengthen CP metabolism are in vivo findings of phase II metabolites in bile, and CP degradation to carbon fragments in experimental animals. Still the metabolic transformations of CPs are poorly studied, and no metabolic scheme has yet been presented. Further, toxicokinetic mass balance calculations suggest that a large part of a given dose (not found as parent compound) is transformation products of CPs, and in vitro metabolism studies present numerous CP metabolites (e.g., chloroalkenes, chlorinated ketones, aldehydes, and carboxylic acids).